Assessing the relationship between cognitive dysfunction and brain atrophy in Alzheimer's disease: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Edison, Paul; Femminella, Grazia Daniela; Nowell, Joseph; Raza, Sanara; Livingston, Nicholas R; Blunt, Eleanor G; Carver, Stefan; Holmes, Clive; Ritchie, Craig W; Lawrence, Robert M; McFarlane, Brady; Tadros, George; et al.
Abstract: Background: Brain atrophy can be reliably measured through volumetric analysis of structural MRI and is a valid biomarker of neurodegeneration in Alzheimer's disease (AD) pathology 1 . The Alzheimer's Disease Assessment Scale‐Cognitive subscale (ADAS‐Cog12) is a neuropsychological test designed to assess the level of cognitive dysfunction in AD within cognitive domains such as memory 2 . This study aimed to assess the relationship between brain atrophy and ADAS‐Cog12 score in patients with AD. Methods: 172 patients with mild‐to‐moderate Alzheimer's disease (Age range 51‐58, Mean=71, SD=+/‐8) underwent a T1‐weighted MPRAGE MRI scan and neuropsychological testing using the ADAS‐Cog12. Volumetric MRI measures extracted using Freesurfer for the hippocampus, medial temporal lobe, temporal lobe and total grey matter were individually correlated with each patient's ADAS‐Cog12 score using Pearson's correlation coefficient following removal of outliers in each data set (+/‐ 2SD from the mean). Results: Increasing ADAS‐Cog12 score was significantly correlated with decreasing volume of the hippocampus ( r =‐0.280, p <0.001), medial temporal lobe ( r =‐0.246, p =0.001), temporal lobe ( r =‐0.300, p <0.001) and total grey matter ( r =‐0.236, p =0.002). Conclusions: This study demonstrated that the ADAS‐Cog12 correlated with AD‐related regional brain atrophy, suggesting that ADAS‐Cog could be used as an outcome measure in AD trials and reflects underlying neuronal damage along with cognitive function.